2011
DOI: 10.1074/jbc.m111.286161
|View full text |Cite
|
Sign up to set email alerts
|

GTP-dependent Binding and Nuclear Transport of RNA Polymerase II by Npa3 Protein

Abstract: Background:The mechanism underlying nuclear transport of RNA polymerase II (RNAPII) is unclear. Results: Npa3 is required for nuclear localization of RNAPII and binds it in a GTP-dependent manner. Conclusion: RNAPII nuclear import takes place via an unconventional pathway involving Npa3 and a cycle of GTP-dependent Npa3-RNAPII binding and release. Significance: Learning the mechanism of RNAPII nuclear import is crucial for understanding the regulation of gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 32 publications
3
59
2
Order By: Relevance
“…In addition, a single Q110L mutation, predicted to disrupt buttressing of the GPN loop by residue Q110 in motif G3, was also inactive. All mutated residues shown here to be involved in catalysis in vitro are essential in vivo (7,21). Furthermore, purified Npa3 formed a dimer, and in the Npa3-GDP crystals, two symmetry-related complexes formed a dimer that contained the GPN loop of one monomer in the active site of the other monomer, as observed for the archaeal structure.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…In addition, a single Q110L mutation, predicted to disrupt buttressing of the GPN loop by residue Q110 in motif G3, was also inactive. All mutated residues shown here to be involved in catalysis in vitro are essential in vivo (7,21). Furthermore, purified Npa3 formed a dimer, and in the Npa3-GDP crystals, two symmetry-related complexes formed a dimer that contained the GPN loop of one monomer in the active site of the other monomer, as observed for the archaeal structure.…”
Section: Resultsmentioning
confidence: 64%
“…Depletion of human GPN3 (20) or mutation of yeast GPN2 or GPN3 (12) also leads to the cytoplasmic accumulation of Rpb1, indicating a general role of all three GPN-loop GTPases in Pol II biogenesis. Depletion of the GPN1 homolog Npa3 from the yeast Saccharomyces cerevisiae leads to the cytoplasmic accumulation of Rpb1 and Rpb3 (21). Rpb1 accumulation is also observed when Npa3 is mutated in its nucleotide-binding site or GPN motif (7,21).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Assembly of the RNA polymerases in both humans and yeast is proposed to occur in the cytoplasm as a prerequisite for their nuclear import with the action of several factors (23,30,32,(60)(61)(62). However, little is known about the disassembly, degradation, and recycling of the RNA polymerases.…”
Section: Discussionmentioning
confidence: 99%
“…Rpb2/Rpb3 remain associated, and Rpb6 may associate with this intermediary, pointing to the action of an assembly factor, which could be the prefoldin Bud27. Reassociation of different subunits in the cytoplasm with newly synthesized Rpb1 occurs sequentially, involving different assembly and transport factors (30,32,(60)(61)(62); it is suggested that Bud27 acts in a final step for correct assembly of Rpb5 (23). Whole RNA pol II associated with assembly and transport factors enters the nucleus, and these shuttle it again to the cytoplasm, some of them by a Crm1-dependent mechanism, Bud27 by a Crm1-independent mechanism (23).…”
Section: Fig 10mentioning
confidence: 99%